Utilisation and perceptions towards smart device visual acuity assessment in Australia: a mixed methods approach. Issue 3 (23rd March 2019) - Keel, Stuart; Scheetz, Jane; Holloway, Edith; Han, Xiaotong; Yan, William; Mueller, Andreas; He, Mingguang
Abstract : Objectives: To investigate mobile health product use in Australia and societal and clinician perceptions towards smartphone based visual acuity (VA) assessment tools. Design: Quantitative analysis of a cross-sectional survey delivered to the general public and thematic analysis of in-depth interviews of eye health clinicians. Setting: Online survey within Australia and face-to-face in-depth interviews of clinicians. Participants: 1016 adults were recruited via Survey Monkey Audience, social media (Facebook and Twitter), Rotary Australia and Lions Clubs Australia. Six clinicians were recruited from private and public settings in Melbourne, Australia. Primary and secondary outcome measures: The study assessed socio-demographic characteristics, history of mobile health product use and perceived advantages and potential drawbacks of smartphone based VA assessment tools. Results: A total of 14.4% of the study population had previously used a mobile-based health product. After adjusting for covariates, younger age (p=0.001), male gender (p=0.01) and higher income (>$45 000) were associated with increased likelihood of having used a mobile health product (p=0.005). Seventy-two per cent of participants would use an automated smartphone based VA assessment tool, provided that the accuracy was on par to that of human assessors. Convenience (37.3%) and cost-savings (15.5%) were ranked as the greatest perceived advantages. While test accuracy (50.6%), a lack of personal contact with healthcare providers (18.3%) and data security (11.9%) were the greatest concerns. Themes to emerge from clinician qualitative data included the potential benefits for identifying refractive error in patients, as well as the ability to self-monitor vision. Concerns were raised over the potential misuse of self-testing vision apps and the inability to detect pathology. Conclusion: Our findings suggest that a substantial proportion of the Australian population do not use mobile health products. Furthermore, there remains notable concerns, including test accuracy and data privacy, with smartphone-based VA assessment tools by both clinicians and the public.